Diagnosis and Classification of Acute Leukemia in Bone Marrow Trephine Biopsies, Utility of a Selected Panel of Minimal Immunohistochemical Markers - Priya Subashchandrabose; Lakshmikanth Ramiah Madanagopaal; Tadury Madhukar Subba Rao (International Journal of Hematology-Oncology and Stem Cell Research, 2016)
Background: Acute leukemias are characterized by neoplastic proliferation of hematopoietic stem cells and accumulation of blasts and immature cells in the bone marrow. We applied a selective panel of immunohistochemical markers on bone marrow trephine tissue sections and observed their utility in diagnosis and typing of acute leukemia. Materials and Methods: The study was done at PSG institute of medical sciences and research from 1st January, 2008 to 30th June, 2012. Immunohistochemistry was done to detect the expression of Myeloperoxidase (MPO), Terminal deoxynucleotidyl transferase (TdT), Cluster of Differentiation 3 (CD3) and Cluster of Differentiation 20 (CD20). Results: On an average, 76 new cases of leukemia are diagnosed each year in our hospital. Of these 28.7% are acute leukemias, which had a bimodal peak age of occurrence with almost equal sex distribution. Only 9 cases could be typed as Acute Myeloid Leukemia (AML) or Acute Lymphoid Leukemia (ALL) purely by morphology. Another 10 cases were typed using cytochemistry. Immunohistochemical panel helped to type 90% of cases. We also identified 1 case of AML of ambiguous lineage. The data were analysed statistically using SPSS version 21 and found out that the immunohistochemistry was found to be extremely significant (p<001) by Chi-Square test. Conclusions: Based on our results, we suggest the use of this limited panel of markers for routine evaluation of all acute leukemias. It is easier to type using Immunohistochemistry rather than flowcytometry, given the disadvantage of the costs involved with the latter.